HIV-Associated Histoplasmosis: Current Perspectives - Myint T (Dove Medical Press, 2020)
Thein Myint,1 Nicole Leedy,1 Evelyn Villacorta Cari,1 L Joseph Wheat2 1Division of Infectious Diseases, Department of Internal Medicine, University of Kentucky, Lexington, KY, USA; 2MiraVista Diagnostics, Indianapolis, IN, USACorrespondence: Thein MyintDivision of Infectious Diseases, Department of Internal Medicine, University of Kentucky, Lexington, KY 40536, USATel +1 859-323-8178Fax +1 859-323-8926Email thein.myint3@uky.eduAbstract: Histoplasmosis is an endemic mycosis caused by Histoplasma capsulatum. Infection develops by inhalation of microconidia from environmental sites inhabited by birds and bats. Disseminated disease is the usual presentation due to impaired cellular immunity. Common clinical manifestations include fever, fatigue, malaise, anorexia, weight loss, and respiratory symptoms. Histoplasma antigen detection is the most sensitive method for diagnosis. The sensitivity of the MVista® Quantitative Histoplasma antigen enzyme immunoassay is 95– 100% in urine, over 90% in serum and bronchoalveolar lavage (BAL) antigen and 78% in cerebral spinal fluid (CSF). A proven diagnosis can be established by culture or pathology with sensitivities between 70% and 80%. The sensitivity of antibody detection by immunodiffusion or complement fixation was between 60% and 70%. Diagnosis using molecular methods has not been adequately validated for implementation and FDA cleared assays are unavailable. Liposomal amphotericin B should be used for 1– 2 weeks followed by itraconazole for at least one year until CD4 counts are above 150 cells/mm3, HIV viral load is below 400 copies/mL and Histoplasma urine antigen is negative. Serum itraconazole level should be monitored to avoid drug toxicity. Antigen should be measured periodically to establish that treatment is effective and to assist in identifying relapse. The incidence of immune reconstitution inflammatory syndrome is low but it must be considered in patients who are thought to be failing antifungal treatment as it does not respond to changing antifungal agents but rather to initiation of corticosteroid therapy. In this review, we discuss pathogenesis, clinical manifestations, diagnosis and treatment based on personal experience and relevant publications.Keywords: histoplasmosis, HIV